2014
DOI: 10.1007/s00423-014-1169-7
|View full text |Cite
|
Sign up to set email alerts
|

Pure laparoscopic liver resection reduces surgical site infections and hospital stay. Results of a case-matched control study in 50 patients

Abstract: In adequately selected patients, laparoscopic hepatectomy is feasible, safe, shortens hospital stay, and decreases surgical site infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The incidence of transumbilical wound infections in Lap-H was 0% (0/42). Similarly, several studies have reported incidence rates of 0-11.8% (11)(12)(13)(14)(15)(16)(17). Thus, our results are comparable to previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of transumbilical wound infections in Lap-H was 0% (0/42). Similarly, several studies have reported incidence rates of 0-11.8% (11)(12)(13)(14)(15)(16)(17). Thus, our results are comparable to previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…Since the first report of a successful laparoscopic liver resection (LLR), diffusion of the laparoscopic approach in liver surgery has been slow because of initial concerns regarding operative risks, oncological issues and technical difficulties. Nevertheless, laparoscopy has now been shown to provide several advantages over laparotomy, including diminished blood loss, fewer complications and ascites, as well as shorter hospital stays. These benefits are thought to be related to the pneumoperitoneum, which limits blood loss and may enhance inflow occlusion when prior selective vascular inflow control is performed, but are also related to the absence of a large incision.…”
Section: Introductionmentioning
confidence: 99%
“…Use of silk sutures (14), postoperative bile leakage (3, 9, 15, 16), failure of the remnant liver (9), portal vein resection (1), preexisting bilioenteric anastomosis (17), and, interestingly, perioperative peritoneal lavage (18) have all been associated with increased rates of OSIs. In contrast, use of broad spectrum antibiotics in chemoprophylaxis (17) as cefuroxime alone confers no protection (19), employment of minimally invasive techniques (20), and avoidance of postoperative bile leak through the air leak test (21) seem to confer a prophylactic effect. Preexisting chronic liver disease and cirrhosis (22) and ERCP and stenting of the common bile duct (17) seem to have no effect on either SSI or OSI.…”
Section: Discussionmentioning
confidence: 99%